Evaluation Of Circular Array Antenna For Mobile Base Station To Increase Reverse-Link Capacity (مجلة المنصور, 2022)
Circular phase array antenna has wide application in Mobile communication system for object to increase system capacity throughreduction of co-channel interference caused by a single cell adjacent cell. These improvements in system capacity depend mainly on the antenna beam pattern and directivity and the process is a kind of spatial filtering, known by Space Division Multiple Axes (SDMA). In this paper a theoretical calculation and MAT-LAB simulation was performed to evaluate beam pattern and antennadirectivity considering different design parameters such as number of radiator element, circle radius, excitation current distribution, and beam scanning. This paper show also through MAT-LAB calculation that by adopting such circular array antenna in Mobile Base Station, leads to improve the reverse-link capacity for a typical Direct Sequence Code Division Multiple Access (DSCDMA)cellular mobile communication system.